### Similar presentations

Thanks to Mr. Ravi, B.T. Asst, GHS, Arangaladurgam.

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20
– 1 +1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 (x + 1) oR k/r]` – 1 +1 + 13
– 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)

+ k/r]`pfpDtfTk: x3 + 13x2 + 32x + 20 k/r]`kqf = (x + 1) oR k/r]` – 1
+1 + 13 + 32 + 20 – 12 – 20 (x + 1) oR k/r]` + 1 + 12 x2 + 12x <p.p. \$. p. + 12 = + 2x + 10x + (X x X) + (2 x X) + (2x5xX) + (2x2x5) (+21) X (X+2) + 5 + 2 + 10 (+12) (X + 2) (X + 5) k/r]`kqf = (X + 1) (X +5)